The risk implications of the business loan activity in credit unions - Gomez-Biscarri, Javier; López-Espinosa, Germán; Mesa-Toro, Andrés (Journal of Financial Stability, 2021)
US credit unions have been subject to a strict regulation of their commercial lending which included both requirements for enhanced organizational practices and a cap on the proportion of business loans relative to assets (imposed in 1998 by US Congress). Since 2003, however, these limitations have been steadily relaxed, a process which has resulted in an increase in credit union business lending activity. Using data from the universe of US credit unions we provide comprehensive evidence that expansion of the business loan portfolio increases the risk of the asset side of the credit union. This is the case even for credit unions which benefit from partnership with the SBA, for which we observe an initial increase in the risk of non-SBA backed loans (an overconfidence effect) which reverses over time (a learning effect). Our results suggest, furthermore, that the risk of business loans is exacerbated for credit unions which initiate their business loan activity and which do so rapidly. In the second part of our analysis we provide descriptive and quasi-experimental evidence that expansions of credit union activity into business loans are associated with lower subsequent growth rates of deposits. This result is similar to the reaction to risk indicators found in the banking literature and might give an ex-ante incentive for the CU that could work as a market-based stabilization mechanism complementary to that of explicit regulation.